Distinct deficits of repetition priming following lateral versus anteromedial frontal cortex damage. (6th June 2022) - Milleville, Shawn C.; Gotts, Stephen J.; Wittig, John H.; Inati, Sara K.; Zaghloul, Kareem A.; Martin, Alex
Abstract: Object repetition commonly leads to long-lasting improvements in identification speed and accuracy, a behavioral facilitation referred to as "repetition priming". Neuroimaging and non-invasive electromagnetic stimulation studies have most often implicated the involvement of left lateral frontal cortex in repetition priming, although convergent evidence from neuropsychological studies is lacking. In the current study, we examine the impact of surgical resection for the treatment of epilepsy on the magnitude of repetition priming at relatively short-term (30–60 min delay) and long-term (3 months) delays in 41 patients with varying seizure foci and resection locations. Overall, patients exhibited significant repetition priming at both short-term and long-term delays. However, patients with frontal resections (largely anterior and medial frontal) differed significantly from those with right anterior temporal resections in showing fully intact short-term priming but absent long-term priming. In a comparison set of 10 recovered aphasic patients, patients with left lateral frontal damage exhibited impaired short-term priming relative to other frontal damage locations, suggesting the differential involvement of lateral and anteromedial frontal regions in mediating repetition priming at short-lag and long-lag timescales, respectively. Highlights: Effect of surgical resection/stroke on long-term repetition priming investigated. Priming selectively impaired at 3 months with anteromedial frontal removal. Shorter-term priming (30-min) impaired instead with lateral frontal damage. Priming effects unrelated to individual variability in explicit memory or etiology.